2018
DOI: 10.1021/acsaem.8b00778
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine-Based Polymer Cathode Materials with Ultrahigh Power Densities for Lithium Ion Batteries

Abstract: Lithium ion batteries (LIBs) currently deliver the highest energy density of any known secondary electrochemical energy storage system. However, new cathode materials, which can deliver both high energy and power densities, are needed to improve LIBs. Herein, we report on the synthesis of a new organic-based redox-active material centered about phenothiazine and phenylenediamine units. Improved Coulombic efficiencies and greater capacity retention during cycling are observed through the copolymerization of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…In our previous study on cross‐linked poly(phenothiazine–dimethylphenylenediamine), we observed that, above a certain threshold of cross‐linking density, rate performance declined as a result of lowered ionic transport through the material . Therefore, two molar ratios of 4 and 5 were examined to determine a cross‐linking density that would mitigate dissolution while retaining high ion diffusion (Table , entries 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study on cross‐linked poly(phenothiazine–dimethylphenylenediamine), we observed that, above a certain threshold of cross‐linking density, rate performance declined as a result of lowered ionic transport through the material . Therefore, two molar ratios of 4 and 5 were examined to determine a cross‐linking density that would mitigate dissolution while retaining high ion diffusion (Table , entries 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Cross‐linking can disrupt ordering and restrict polymer mobility to ensure an open, amorphous structure even in the swelled state. Recently, we reported on a cathode material with 3,7‐diamino‐substituted phenothiazines as charge‐storage elements . In that study, cross‐linking of a linear energy storage polymer led to improved stability on cycling, higher discharge capacity, and improved rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…Another redox‐active group with a similar oxidation potential is phenothiazine (PT). We, among other groups, have investigated PT‐based polymers as cathode materials. In particular poly(3‐vinyl‐ N ‐methylphenothiazine) (PVMPT) showed excellent results regarding cycling stability and rate capability .…”
Section: Figurementioning
confidence: 99%
“…Peterson et al. followed this strategy and combined phenothiazine with phenylenediamine units, allowing capacity values of 150 mAh g −1 and high voltages (2.8–4.3 V vs. Li/Li + ) . On the other hand, polyimides containing naphthalene or pyromellitic moieties have been widely investigated as anode materials not only for Li‐ or Na‐ion batteries but also for other alkali‐ion batteries, such as Ca and Mg .…”
Section: Introductionmentioning
confidence: 99%